A holistic, learning-centred approach to building evaluation capacity in development organizations. (July 2015) - Lennie, June; Tacchi, Jo; Wilmore, Michael; Koirala, Bikash
There is growing pressure on development organizations to improve their evaluation systems and capacities. This presents considerable challenges for time- and resource-poor organizations in developing countries. Evaluation capacity development (ECD) approaches are needed that are appropriate and effective for such organizations. We argue that this requires a long-term, holistic, participatory, learning-centred approach that aims to develop learning organizations and build the capacity of whole organizations and their stakeholders. It also needs to incorporate local knowledge and ideas and ongoing meta-evaluation of ECD activities. We describe this approach and how it was applied in a four-year action research project with a non-governmental organization in Nepal. Drawing on findings from this project and various follow up activities, we suggest some principles and strategies for designing and implementing an effective and sustainable approach to ECD that can help to address the many challenges and issues we have identified.